The bookseller who wrote prefaces (and the stolen books); the prefaces of Francisco Rolland and book circulation in the Portuguese Empire at the end of the 18th Century - DeNipoti, Claudio (História: Questões e Debates, 2017)
This article browses the writings of French bookseller and printer stablished in Lisbon, Francisco Rolland, who wrote paratexts in his editions, such as prefaces, introductions, warnings to the reader and newsletters, in which he makes discursive patterns relating to the fundamental questions around the Portuguese book trade in the 18th Century: utility, need, instruction, and service to the Empire. At the same time, Rolland was an apt merchant, who knew how to foresee the changes in taste and the demands of the book trade, while dealing with the censorship machinery in order to publish and market his books. This work tries to understand how this agent of the book acted in the wider context of the Portuguese Enlightenment.